Família e escola na contemporaneidade: os meandros de uma relação. - Nogueira, Maria (2008)
The article approaches the contemporary tendencies of intensification of the interactions between family and school and the wide social visibility of this phenomenon. It examines the factors that are in the origin of this movement, as it is known: the changes in the institution of family in contemporary times on one hand, and in the school system on the other hand. It also emphasizes some characteristics involved in the current family-school relationship and calls attention to the risk of taking the “partnership” idea among those two socialization instances, as unquestionable evidence. Finally, the paper argues for the need to problematize this phenomenon with sociological findings that point out the differences among families belonging to different social environments.